2021
DOI: 10.1097/md.0000000000026430
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to pesticides during pregnancy and risk for attention-deficit/hyperactivity disorder in offspring

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is the most common psychiatric disorder in childhood. Studies explored the association of maternal exposure to pesticides during pregnancy with a risk of offspring developing ADHD, but have reported inconclusive results. Here, we will perform a systematic review and meta-analysis of observational studies to assess a possible association between them. Methods: This study followed the Preferred Reporting Items fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Being the most common psychiatric disorder in children, ADHD often persists into adulthood and is estimated to affect approximately 5% of children under 18 and 2.5% of adults worldwide [2,3]. ADHD is associated with a wide range of other mental health problems, including mood disorders, personality disorders, antisocial behavior, self-harm, and substance abuse [4]. In children, ADHD can disrupt social life and sometimes lead to poor educational performance and integration difficulties [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being the most common psychiatric disorder in children, ADHD often persists into adulthood and is estimated to affect approximately 5% of children under 18 and 2.5% of adults worldwide [2,3]. ADHD is associated with a wide range of other mental health problems, including mood disorders, personality disorders, antisocial behavior, self-harm, and substance abuse [4]. In children, ADHD can disrupt social life and sometimes lead to poor educational performance and integration difficulties [2].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of ADHD has not yet been well-defined, but it is suggested that is an inherited disorder, with an estimated heritability of 70% to 80% [4]. The increasing prevalence of ADHD in recent decades has led to the hypothesis that environmental factors may also contribute to the development of ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Attention deficit hyperactivity disorder is a neurobiological condition characterized by impaired attention, impulsivity, and hyperactivity that often begins in childhood and frequently persists into adulthood [1]. The idea is well-expressed in this quote by Sarah Young, which says, "living with ADHD is like being locked in a room with 100 televisions and 100 radios all playing.…”
Section: Introductionmentioning
confidence: 99%
“…None of them have power buttons so you can turn them off and the door is locked from the outside" [2]. ADHD affects around 5% of children under 18 and 2.5% of adults worldwide [1]. It is also associated with other mental health problems, such as personality disorders and substance abuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation